Taxonomic revision of Allium cyathophorum (Amaryllidaceae) - Li, Min Jie; Liu, Jian Quan; Guo, Xian Lin; Xiao, Qun Ying; He, Xing Jin (Phytotaxa, 2019)
Our integrated evidence indicates morphological and genetic polymorphisms in Allium cyathophorum and thus the need for a taxonomic revision. First, A. cyathophorum var. farreri is reinstated as A. farreri. Second, a cryptic allotetraploid population geographically confined to the intermediate zone between A. cyathophorum and A. farreri is described here as a new species named A. tetraploideum. Morphological characters that differentiate these three species from each other, as well as information on their distribution range and habitat, are provided.